MENGGUNAKAN METODE CERTAINTY FACTOR SISTEM PAKAR DIAGNOSIS PENYAKIT UMUM PADA KUCING - Sabar, Muhamad; Nurmala, Farida; Kholiq, Abdul (Universitas Majalengka, 2025)
Cats are pets that are susceptible to various diseases if not properly cared for, especially if the owner does not recognize the symptoms of disease in cats, potentially leading to incorrect treatment and worsening the cat's health condition. This study uses an expert system website to diagnose diseases in cats, using the Certainty Factor (CF) method. Certainty Factor is a method used to determine whether a fact has certainty or uncertainty, in the form of a metric that is generally applied in expert systems. This method is used to predict the possibility of disease based on symptoms inputted by the user, so that it can provide initial diagnosis results. The results of the study then conducted a questionnaire to see the usefulness of the system and obtained the results that 91.32% of respondents felt this system was appropriate and useful. In the future, it is hoped that this system can be developed with suggestions for initial treatment or appropriate medication for cats.